Knowledge and information sources of parents of 3‑ to 6‑year-old children concerning skin cancer risk factors - Uter, Wolfgang; Fießler, Cornelia; Gefeller, Olaf; Pfahlberg, Annette Bettina (Bundesgesundheitsblatt, Gesundheitsforschung, Gesundheitsschutz, 2017)
BACKGROUND: The dissemination of knowledge on risk factors and preventive strategies is a core element of skin cancer prevention. However, little is known about the information channels utilised by the population for this purpose. OBJECTIVES: Descriptive analysis of information sources used by parents of 3‑ to 6‑year-old children as a particularly relevant target group and analysis of association patterns between socio-demographic factors, types of information sources and acquired knowledge. MATERIALS AND METHODS: A cross-sectional study was performed using a self-administered questionnaire with an online option between October 2011 and February 2012 with 3129 families who had at least one child visiting a kindergarten in the county of Erlangen-Höchstadt, the city of Erlangen or the city of Ansbach (Bavaria, Germany), with an 87.5% response rate on the level of kindergartens and 56.5% on the level of observational units (families). RESULTS: There were few structural differences between study regions. The internet was used by only 13.3% of participants. A positive association was found between the use of multiple information sources and relevant knowledge and, partly, protective behaviour. A negative association was identified between the use of the internet and knowledge. In contrast, the use of print media or audio-visual or personal channels of information was positively associated with knowledge. CONCLUSIONS: Preventive efforts should be increased that target parts of the population with lower formal education. The internet does not seem to play an important role and may even adversely affect knowledge, possibly due to unvalidated and misleading information.
EVALuna2:34181